Assessing the efficacy of camera trapping as a tool for increasing detection rates of wildlife crime in tropical protected areas. (September 2016) - Hossain, Abu Naser Mohsin; Barlow, Adam; Barlow, Christina Greenwood; Lynam, Antony J.; Chakma, Suprio; Savini, Tommaso
Abstract: The future of biodiversity in Asia is increasingly dependent on networks of effective protected areas. Three wildlife sanctuaries of the Bangladesh Sundarbans are typical examples of protected areas where detection and monitoring of threats is difficult due to low densities of patrol staff and low frequency of patrolling relative to the area that requires monitoring. The aim of this study was to use camera traps to quantify: 1) the levels of different types of illegal human activities (IHA), 2) spatio-temporal variation in illegal human activities, and 3) what proportion of camera trap records can be used to identify perpetrators. Each photograph was categorized as either illegal human activity (IHA) or legal human activity (LHA) based on interpretation of the particular human activity and equipment observed in photograph. For IHA, infraction type was based on the Bangladesh Wildlife (Conservation and Security) Act 2012. A total of 914 unique human activity events were recorded (872 IHA and 42 LHA) in camera trap photos over a total of 1039 trap nights. The best model suggests that during spring tide 91% of camera trapped locations in the West Sanctuary had IHA occurring in them during the survey period, while 84% and 74% locations had IHA in the South Sanctuary and East Sanctuary respectively. Camera trapping in remote areas can potentially help protected area managers to increase rates of detection of IHA in their conservation landscapes and increase rates of arrests and prosecutions by providing appropriate supporting evidence.